Mihail Bahtin in OBERIU/OBERIU - Javornik, Miha (Slavistična revija, 1999)
The article compares the alayses of the Russian thinker Mikhail Bakhtin with literature by the late avant-garde group called" Oberiu" (OBERIU - Ob'edinenie rael'nogo iskusstva). There are parallels between their understanding of the world in the 1920's. The question in whether their similar views in the understanding of culture and the position of an individual/artist in it, respectively, are a coincidence, a result of an acquaintance between them, or they had similar attitude towards the reality, as it was formed at a certain level of the cultural-historical development. The article answers the question whether the similarity in the Oberiuites' reflection of the reality detrimentally influenced Bakhtin's understanding, which as a consequence led to the theory of carnivalization, dialogism and heteroglossia, respectively.
Keywords: avantgarda; Bahtin, Mihail Mihajlovič; literarna zgodovina; OBERIU; ruska književnost